Gene Duplication and the Structure of Eukaryotic Genomes - Friedman, Robert; Hughes, Austin L.

(untitled) (Genome Research, 2001)
A simple method for understanding how gene duplication has contributed to genomic structure was applied to the complete genomes ofCaenorhabditis elegans, Drosophila melanogaster, and yeast Saccharomyces cerevisiae. By this method, the genes belonging to gene families (the paranome) were identified, and the extent of sharing of two or more families between genomic windows was compared with that expected under a null model. The results showed significant evidence of duplication of genomic blocks in both C. elegans and yeast. In C. elegans, the five block duplications identified all occurred intra-chromosomally, and all but one occurred quite recently. In yeast, by contrast, 39 duplicated blocks were identified, and all but one of these was inter-chromosomal. Of these 39 blocks, 28 showed evidence of ancient duplication, possibly as a result of an ancient polyploidization event. By contrast, three blocks showed evidence of very recent duplication, while seven others showed a mixture of ancient and recent duplication events. Thus, duplication of genomic blocks has been an ongoing feature of yeast evolution over the past 200–300 million years.